The Ballad of the Lone Medievalist - Tracy, Kisha G.; Sexton, John P. (punctum books, 2018)
Are you a Lone Medievalist? Working medievalists are often the only scholar of the Middle Ages in a department, a university, or a hundred-mile radius. While working to build a body of focused scholarly work, the lone medievalist is expected to be a generalist in the classroom and a contributing member of a campus community that rarely offers disciplinary community in return. As a result, overtasked and single medievalists often find it challenging to advocate for their work and field. As other responsibilities and expectations crowd in, we come to feel disconnected from the projects and subjects that sustain our intellectual passion. An insidious isolation even from one another creeps in, and soon, even attending a conference of fellow medievalists can become a lonely experience. Surrounded by scholars with greater institutional support, lower teaching loads, or more robust research agendas, we may feel alienated from our work - the work to which we've dedicated our careers.